(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Vomiting after surgery and pain are frequent adverse effects after pediatric adenotonsillectomy, which result in delayed recovery, dehydration, and analgesic misuse. Gabapentin used preoperatively has demonstrated encouraging analgesic and antiemetic effects in different operative departments. Objective: To assess the effectiveness of pre-operative gabapentin in the prevention of postoperative vomiting and analgesic needs after pediatric adenotonsillectomy. Methods: It was a randomised controlled trial that involved 64 children who were between the ages of 4 and 12 years and were undergoing adenotonsillectomy. Gabapentin or a placebo was assigned to the patients. Oral gabapentin 20mg/kg was given one hour prior to surgery to the gabapentin group. The 12-hour monitoring of postoperative vomiting and analgesic needs was done. Data were calculated by means of SPSS, and p < 0.05 was taken to be significant. Results: The percentage of postoperative vomiting was reduced in the gabapentin group (25) than in the placebo group (53), and fewer children were in need of rescue analgesia (22 vs. 50). The pain scores were always lower with the use of gabapentin. Conclusion: Preoperative gabapentin is effective in the reduction of postoperative vomiting and analgesic requirement in pediatric patients with adenotonsillectomy.